Two Intact Executive Capacities in Children with Autism: Implications for the Core Executive Dysfunctions in the Disorder - Russell, James; Jarrold, Christopher; Hood, Bruce (Journal of autism and developmental disorders, 1999)
Two studies examined executive functions in children with autism. Results indicated that subjects performed like normally developing children when either no arbitrary and novel rules were involved or the output was verbal. Results support the hypothesis that these children are challenged by executive tasks because they are unlikely to encode rules in verbal form. (Author/DB)